The role of coaching and coach language in clients’ language and individual change - Barbara Fölscher-Kingwill; Nicky Terblanche (International Journal of Evidence Based Coaching and Mentoring, 2019)
This study explored the under-researched area of the effect of coaching on clients’ spoken and internal language, the link to individual change, as well as the effect of coach language on client language. Using a qualitative, phenomenological approach, 12 in-depth interviews were conducted with coaches, and clients who were business leaders. The findings, derived through thematic analysis suggest that coaching plays a role in changing clients’ language and that this language change may be linked to individual change. Furthermore, coach language and linguistic techniques are instrumental in client language change.